P05.58 Active beam scanning proton therapy for large skull base benign meningiomas: early outcomes. (19th September 2018) - Scartoni, D; Amelio, D; Lorentini, S; Widesott, L; Fellin, F; Donner, D; Giacomelli, I; Schwarz, M; Chierichetti, F; Farsad, M; Amichetti, M
Abstract: Background: To report preliminary results of active beam scanning proton therapy (PT) for large skull base benign meningiomas. Material and Methods: Thirty-three patients (pts) with large skull base meningiomas were treated with PT between January 2015 and February 2018. Median age was 53 years (range, 28–82) while KPS ranged between 60 and 100 (median 90); 26 were female (79%), and 7 were male (21%). Twelve pts (36%) had histologically proven World Health Organization (WHO) Grade I tumors. In remaining pts diagnosis was based on the typical imaging appearance of benign meningioma. All patients received PT for residual, progressive or non-operable lesions. Newly diagnosed tumors received total dose of 50 GyRBE (RBE: relative biologic effectiveness) while progressing meningiomas 54 GyRBE. All the treatments were delivered at 2 GyRBE per fraction. Treatment planning was based on morphological magnetic resonance imaging (MRI) with contrast enhancement medium administration. All pts received also 68-Ga-DOTATOC-PET. Any area of contrast enhancement on MRI was used to identify the gross tumor volume. We used the pathological distribution of 68Ga-DOTATOC in brain tissue to identify the so-called Biological Tumor Volume. Gross tumor volume ranged from 21 to 107 cc. Toxicity was assessed according to Common Terminology Criteria for Adverse Events version 4.0. Median follow-up time was 9 months (range, 3–37). Results: All pts completed the treatment without breaks. Acute side effects include grade 1 (21%) and grade 2 (9%) skin erythema, grade 1 (9%) and grade 2 (9%) alopecia, grade 1 (48%) fatigue, grade 1 (6%) and grade 2 (15%) conjunctivitis, grade 1 (15%) pain, grade 1 (15%) blurred vision, grade 1 (15%) headache, and grade 2 (15%) skin hyperpigmentation. One pt experienced grade 3 pain. There were no further grade 3 or higher acute toxicities. Late side effects include grade 1 (9%) and grade 2 (9%) alopecia, grade 1 (21%) fatigue, grade 1 (9%) and grade 2 (6%) headache, grade 1 (6%) dizziness, grade 1 (6%) blurred vision, grade 1 (6%) and grade 2 (6%) pain, grade 1 (6%) dry eye, and grade 1 (15%) skin hyperpigmentation. One pts experienced grade 3 pain. There were no further grade 3 or higher late toxicities. One pts (3%) with cavernous sinus meningioma experienced complete obstruction of intracavernous carotid artery with mild transient symptoms that resolved in few days and brain tissue ischemia detected at MRI (grade 2). Before irradiation this pts already had a meningioma-related near-complete obstruction of the intracavernous carotid artery and received a vascular surgery evaluation. Currently, absolute tumor control is 100%. Moreover, relief of symptoms recorded before irradiation occurred in 24% of pts. Conclusion: PT is feasible and safe treatment for pts with large skull base benign meningiomas. Longer follow-up is necessary to assess definitive efficacy.